The Relationship between Nurse Knowledge and Completeness of Documentation of Integrated Patient Progress Notes (CPPT) at Ratu Zalecha Hospital, Martapura - Endang Pertiwiwati; Noor Diani; Fitri Ayatul Azlina; Norsas Mita (Lambung Mangkurat University, 2024)
Knowledge is a very important domain in shaping a person's behavior, including in the nursing documentation process. A better level of knowledge of nurses will facilitate decision making when carrying out nursing documentation and increase the implementation of complete documentation. This study aims to determine the relationship between nurses' knowledge and the completeness of integrated patient progress record documentation (CPPT) at Ratu Zalecha Hospital, Martapura. This research uses non-experimental quantitative descriptive. The number of respondents was 87 executive nurses in the inpatient ward at Ratu Zalecha Hospital, Martapura, selected using a cluster random sampling technique. Data collection was carried out by distributing questionnaires and observing directly on the CPPT sheet. The research results show that the p value = 0.000, which means that H0 is rejected and Ha is accepted. So it can be concluded that there is a relationship between nurse knowledge and completeness of integrated patient progress record documentation (CPPT) at Ratu Zalecha Hospital, Martapura.